2013
DOI: 10.1063/1.4772621
|View full text |Cite
|
Sign up to set email alerts
|

A grillage model for predicting wrinkles in annular graphene under circular shearing

Abstract: Strengthening metal nanolaminates under shock compression through dual effect of strong and weak graphene interface Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…In this framework the differences in wrinkling pattern between graphene and graphynes were analysed. It was found that the wave numbers of graphene remain constant, i.e., 9, from the wrinkling initiation to the first bond breaking, which is consistent with previous research [38]. It must be pointed out that the ratios of outer-to-inner radius can affect the wave number.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In this framework the differences in wrinkling pattern between graphene and graphynes were analysed. It was found that the wave numbers of graphene remain constant, i.e., 9, from the wrinkling initiation to the first bond breaking, which is consistent with previous research [38]. It must be pointed out that the ratios of outer-to-inner radius can affect the wave number.…”
Section: Resultssupporting
confidence: 88%
“…The wrinkling pattern presents decay along the longitudinal direction and indicates a transition from bending to stretching. Hence, from the shape of each wrinkle there is an interchange of bending energy and stretching energy, which is in good agreement with previous research results obtained for annular graphene [38,39].…”
Section: Wrinkle Patternsupporting
confidence: 92%
“…The finite element method has been used in a variety of studies of wrinkling in thin sheets (Zheng 2009;Wong and Pellegrino 2006c;Nayyar et al 2011;Healey et al 2013;Carbonez 2013). There are typically three approaches used: static post-buckling (Zheng 2009;Wong and Pellegrino 2006c), the Riks method (Nayyar et al 2011), and explicit (Zhang et al 2013). The first two rely on an initial analysis to determine the buckling eigenmodes of the sheet.…”
Section: Overview Of Numerical Approachesmentioning
confidence: 99%
“…Zhang et al studied the formation and characteristics of the wrinkles in annular graphene under inplane rotation combing grillage model and molecular dynamics simulation. 32,33 Qin et al investigated the effect of wrinkles on the surface area of graphene using classical molecular dynamics simulations, and suggested that the high specic surface area of graphene can only be affected up to 2% regardless of loading conditions, geometry, and defects. 34 Li et al reported the wrinkling characteristics of surface functionalized graphene and graphyne under circular shearing at the inner edge.…”
Section: Introductionmentioning
confidence: 99%